Interface ciência e religiosidade entre estudantes universitários - Lima, Silmara Maria de (2019)
In this paper I identified the association between intrinsic religiosity and attitudes toward science in college students. In addition, I also checked for differences in the type of undergraduate degree or the year the student was enrolled in relation to the intrinsic religiosity variables; beliefs and affections regarding science; and personal initiative in relation to science. 400 undergraduate students of Biological Sciences courses participated in the research; Physics, geography; Mathematics; Chemistry and Pedagogy of the University Campus Professor Alberto Carvalho / UFS. The sampling was of the non-probabilistic convenience type. Each student answered a standardized questionnaire immediately after reading and agreeing to the free and informed consent form. The questionnaire data were tabulated, treated and statistically analyzed. As a result of the research, we found that the intrinsic religiosity score is very high and does not vary over the course. Thus, in the courses in which there was an association between intrinsic religiosity and attitudes toward science, it was negative and weak. In the same way I observed the existence of significant differences in undergraduate courses in Biological Sciences and Geography, with a higher score of favorable attitudes towards science, compared to courses in Chemistry and Pedagogy, with lower scores.